The Morin transition in nanostructured pseudocubic hematite: effect of the intercrystallite magnetic exchange - Bengoa, Jose Fernando (2010)
The Morin transition in α-Fe2O3 particles with homogeneous pseudocubic morphology of about 1.8 μm side has been studied by different techniques. The particles are made up of nanometric crystallites with a narrow size distribution. Samples annealed at 673, 773 and 873 K, yielded Morin transition temperatures, TM, of about 230, 241, and 245 K, respectively, which are lower than the bulk value, TM ≈ 263 K. In addition, the temperature range ΔTM through which these samples undergo the transition is very narrow with respect to the values reported in the literature. Ranges of 20, 10 and 8 K, were obtained for the samples annealed at 673, 773 and 873 K. In this work, through the estimation of the exchange magnetic energy, we demonstrate that the existence of the Morin transition, and its shift and breadth are related to the presence of intercrystallite interactions within the pseudocubic particles. These intercrystallite interactions are modified by the annealing treatments, which help to remove non-stoichiometric hydroxyl groups and incorporated water molecules. © 2010 Elsevier B.V. All rights reserved.